On the stability of orthogonal bases in non-archimedean metrizable locally convex spaces - Śliwa, Wiesław (The Belgian Mathematical Society, 2001)
It is proved that an orthogonal basis in a non-archimedean metrizable locally convex space E (in particular, a Schauder basis in a non-archimedean Frechet space E) is stable if and only if there is a continuous norm on E. Many others results are also obtained.
Keywords: Orthogonal sequences; Non-archimedean Frechet spaces